2022
DOI: 10.21601/ejosdr/12233
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Emission Characteristics of Compression Ignition Engine Running on a Blend of Cashew Nut Shell Liquid and Biodiesel Produced from Orange Peel

Abstract: This study evaluates the performance and emission characteristics of an orange peel biodiesel blended with cashew nut shell liquid. It investigates the efficacy of cashew nut shell liquid in reducing nitrogen oxide (NOX) emissions resulting from the combustion of the biodiesel, while optimizing its performance.The biodiesel was prepared via transesterification. It was obtained by reacting orange peel oil produced through Soxhlet extraction with methanol in the presence of NaOH. The biodiesel was blended with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The shells are often roasted in a drum as part of the method that is used to extract CNSO. During the roasting process, CNSO seeps out of the shells, which causes them to become brittle (Nuithitikul et al, 2020; Olugasa et al, 2022). To extract all of the CNSO, the shells are baked in baths at temperatures between 180°C and 185°C.…”
Section: Overview Of Cashew and Cnsomentioning
confidence: 99%
“…The shells are often roasted in a drum as part of the method that is used to extract CNSO. During the roasting process, CNSO seeps out of the shells, which causes them to become brittle (Nuithitikul et al, 2020; Olugasa et al, 2022). To extract all of the CNSO, the shells are baked in baths at temperatures between 180°C and 185°C.…”
Section: Overview Of Cashew and Cnsomentioning
confidence: 99%
“…Higher cetane number leads to an increase in the speed of oxidation and thermal cracking rate, which in turn produces lower specific fuel consumption and reduces the emission of unburned HCs (Cataluna & da Silva, 2012). Olugasa et al (2022) reported 54.4 as the orange peel biodiesel cetane number, which is 20.00% more than the type 2 diesel cetane number. At maximum load, B20 was found to have the optimum BSFC rate and is 9.08% lesser than diesel.…”
Section: Brake-specific Fuel Consumptionmentioning
confidence: 99%